Unequal nursing: the impact of China’s public health insurance on nursing services for older adults - Pengfei Zhang; Jinghua Gao (BMC Nursing)
Abstract Background This study examines the relationship between public health insurance and inequality in nursing services for older adults and explores the different impacts of different public health insurance systems in China. Methods Using data from the China Health and Retirement Longitudinal Study, a logistic regression model was used to examine the use of nursing services by people aged 60 years and above. Results The results show that participation in public health insurance can significantly improve the chances of older adults accessing nursing services, with participants being 53.57% more likely than nonparticipants to use nursing services. In addition, older adults enrolled in the Urban Employee Basic Medical Insurance program were 26.49% more likely than those enrolled in the Urban‒Rural Resident Basic Medical Insurance program to utilize nursing services, underscoring the substantial inequalities resulting from the structural differences within the public health insurance system. Conclusions Although public health insurance plays a key role in improving the accessibility of nursing services for older adults, it also exacerbates existing inequalities. China’s health security reform should improve access to nursing services by increasing participation in public health insurance and eliminating discrimination based on status within the insurance framework.